2001
DOI: 10.1086/323341
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatisInfection Induces Mucosal Addressin Cell Adhesion Molecule–1 and Vascular Cell Adhesion Molecule–1, Providing an Immunologic Link between the Fallopian Tube and Other Mucosal Tissues

Abstract: The development of a protective vaccine against the sexually transmitted disease caused by Chlamydia trachomatis may prevent complications associated with insidious infection. Vaccination via the vaginal route may not be practical, and other routes should be investigated. To this end, the adhesion molecules induced on the fallopian tube endothelium during infection with C. trachomatis were characterized. Adhesion molecules were identified in fallopian tube biopsy specimens cultured with 5 x 10(6) infection-for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…Previous in vitro studies revealing expression of adhesion molecules on human Fallopian tube tissue explants infected in vitro with Chlamydia trachomatis suggest that lymphocytes may use multiple adhesion pathways to migrate to human tissues6. We reported a significant upregulation of the mucosal adhesion molecule, MadCAM-1, and also a non-mucosal adhesion molecule associated with inflammation: vascular adhesion molecule-1, VCAM-1.…”
Section: Introductionmentioning
confidence: 60%
See 1 more Smart Citation
“…Previous in vitro studies revealing expression of adhesion molecules on human Fallopian tube tissue explants infected in vitro with Chlamydia trachomatis suggest that lymphocytes may use multiple adhesion pathways to migrate to human tissues6. We reported a significant upregulation of the mucosal adhesion molecule, MadCAM-1, and also a non-mucosal adhesion molecule associated with inflammation: vascular adhesion molecule-1, VCAM-1.…”
Section: Introductionmentioning
confidence: 60%
“…Investigation of murine and human systems have shown that CD4 T cells primed in lymphoid organs which drain mucosal sites increase surface expression of α4β7 integrin, also called the mucosal integrin; whereas those primed in lymph nodes draining peripheral or non-mucosal sites lose α4β7 integrin expression following antigen exposure and instead express P-selectin ligand and accumulate in peripheral tissues4, 5. The human female reproductive tract is a member of the common immune system and expresses the ligand for α4β7 integrin, MAdCAM-16. Thus, mucosal homing mechanisms are likely to control leukocyte entry into the GT.…”
Section: Introductionmentioning
confidence: 99%
“…Previous in vitro studies revealing expression of adhesion molecules on human Fallopian tube tissue explants infected in vitro with Chlamydia trachomatis suggest that lymphocytes may use multiple adhesion pathways to migrate to human tissues. 7 We reported a significant upregulation of the mucosal adhesion molecule, MadCAM-1, and also a non-mucosal adhesion molecule associated with inflammation: vascular adhesion molecule-1, VCAM-1. We also noted the marked increase of additional non-mucosal adhesion molecules; P-selectin and intracellular adhesion molecule-1 (ICAM-1).…”
Section: Introductionmentioning
confidence: 84%
“…We have previously reported that the mucosal adhesion molecule MadCAM and E & P-selectin are increased in the fallopian tube upon infection using the in vitro fallopian tube infection model 7. Although the murine analog which mediates the binding of lymphocytes to E-selectin has not yet been identified, in humans CLA binds to E-selectin.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, about half of the CD4 + memory T cells in the FRT express various levels of integrin α 4 β 7 (Fig S1), Expression of α 4 β 7 marks immune cells that preferentially traffic to the gut lamina propria (LP) and associated lymphoid tissues (GALT) [15], [16]. However, α 4 β 7 high memory CD4 + T cells can also participate in immune responses in the FRT [17][19]. It is noteworthy that α 4 β 7 high CD4 + T cells are highly susceptible to HIV infection and are preferentially infected during the acute phase of SIV infection [20][22].…”
Section: Introductionmentioning
confidence: 99%